Pharmacotherapy of residual excessive sleepiness among continuous positive airway pressure (CPAP) treated patients with sleep apnea. (4th March 2022) - El-Solh, Ali A.; Rudraraju, Avantika; Pasrija, Divij; Bui, Hoang
ABSTRACT: Introduction: Patients with persistent sleepiness after adequate treatment of obstructive sleep apnea (OSA) with nasal continuous positive airway pressure (nCPAP) experience impaired cognition, reduced productivity, and worse quality of life. Although the mechanisms responsible for this phenomenon are not completely understood, neuroimaging studies have identified reduced gray matter in the frontal cortex and alterations in white matter integrity suggestive of axonal and myelin damage. The intermittent hypoxia with resulting oxidative injury is considered a prime culprit behind the loss of wake-promoting catecholaminergic neurons. Areas covered: This narrative review gives an overview of the pathophysiology and approaches to managing patients with residual sleepiness. The authors explore different targeted strategies aimed at improving selection of appropriate pharmacotherapy. Expert opinion: Wake-stimulant medications (modafinil and armodafinil) have demonstrated efficacy in reducing sleepiness in adequately treated OSA. The recent FDA approval of pitolisant and solriamfetol complements the use of modafinil by substituting for direct sympathomimetic agents. The distinctive pharmacologic profile and mode of action of each of these agents offer the opportunity of a personalized approach to the management of this disorder. Further studies should be conducted on the long-term effect of these agents alone or in combination on brain structural and functional changes.